2016
DOI: 10.4172/2167-0420.1000337
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Urinary Incontinence and its Impact on the Quality of Life and Treatment Seeking Behavior among Malaysian Women: A Review

Abstract: Background: Reports of the prevalence of urinary incontinence (UI) in women seem to vary widely globally. This paper attempts to review the current literature on urinary UI, its prevalence, risk factors and quality of life (QOL) amongst Malaysian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…A community-based study in Australia found that half of the men aged 40-80 years reported terminal dribbling. Post-micturition dribbling was the most frequently reported urinary symptom among older men in Sweden 12 .…”
Section: Discussionmentioning
confidence: 96%
“…A community-based study in Australia found that half of the men aged 40-80 years reported terminal dribbling. Post-micturition dribbling was the most frequently reported urinary symptom among older men in Sweden 12 .…”
Section: Discussionmentioning
confidence: 96%
“…It is a much more common problem in women and seems to vary widely. Dhillon et al [1] provided significant information about the UI, its prevalence, risk factors and quality of life among Malaysian women. To access this, they selected Scopus and Medline search, but the information collected is incomplete and inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of urinary incontinence in this group was 31.3%, with an incidence rate over 1 year of 14.5% and a remission rate of 11.0% [14]. For participants aged 60 or older, self-reported questionnaires were used to measure urinary incontinence, which was defined as involuntary loss of urine during daily activities [15]. The prevalence of urinary incontinence in this group was 29.8%.…”
Section: Methodsmentioning
confidence: 98%